PENDELEGASIAN KEWENANGAN PENDAFTARAN, PEMERIKSAAN BUKTI-BUKTI DAN MENDENGAR KETERANGAN AHLI PERKARA HAK UJI MATERIL SECARA TERBUKA PADA PTUN ATAU PT TUN - Sintara, Dani (Asosiasi Pengajar Hukum Tata Negara dan Hukum Administrasi Negara (APHTN-HAN) Sumatera Utara, 2022)
The issue of judicial review authority conducted in the State Administrative Court in conducting testing of provincial regulations and district/city regulations is different, but testing in the State Administrative Court has not been openly implemented. The research method used is normative juridical. The results of the study showed that the Judicial Review of the District / City Regional Regulation was delegated to the State Administrative Court. Judicial Review of Provincial Regional Regulations is delegated to the High Court of State Administration so that it must be carried out openly, presenting the parties, examination of evidence, witnesses, and experts and the pronouncement of verdicts that are open to the public